Analisis Efektivitas Kegiatan Kolase terhadap Pengembangan Kemampuan Motorik Halus Anak Usia Dini di RA Nurul Islam Ranugedang - Marnia, Rovita (Education Reserach Center, 2025)
This study aims to analyze the effectiveness of collage activities in enhancing fine motor skills in early childhood children at RA Nurul Islam Ranugedang. Early childhood, known as the golden age, is a critical period in the physical and psychological development of children, where fine motor skills play a significant role in preparing children for more complex activities such as writing and drawing. This research uses a quasi-experimental design with a pretest-posttest approach, where children were engaged in collage activities for seven consecutive days. The results show a significant improvement in the children's fine motor skills, with the average score increasing from 4.9 in the pretest (Beginner Category) to 9.2 in the posttest (Developing as Expected Category). These findings indicate that collage activities are effective in stimulating the development of fine motor skills in early childhood, making it a fun and educational method for supporting children's overall growth and development.